ZIF-derived Co–N–C ORR catalyst with high performance in proton exchange membrane fuel cells - Wang, Ruixiang; Zhang, Pengyang; Wang, Yucheng; Wang, Yuesheng; Zaghib, Karim; Zhou, Zhiyou (Progress in natural science, 2020)
Metal and nitrogen-doped carbon (M-N-C) materials have been considered as the most promising non-precious metal oxygen reduction (ORR) catalysts to replace expensive Pt catalysts. Due to high Fenton catalytic activity of Fe element and the resulting instability, Co-based N–C (Co–N–C) catalysts without Fenton catalytic activity should be a worthier ORR catalyst being explored. Although the high ORR activity of Co–N–C catalyst has been demonstrated in aqueous half-cell tests, their performance under PEMFC working condition is still far away from that of state-of-the-art Fe–N–C catalysts. In this study, a high-performance Co–N–C catalyst was synthesized by one-step pyrolyzing Co-doped ZIF-8 (zeolitic imidazolate framework-8) particles in-situ grown on the high-surface-area KJ600 carbon black with high electronic conductivity. The resulting Co–N–C catalyst exhibited high intrinsic ORR activity, fast mass transfer rate and high electronic conductivity, and thus yielded a remarkable peak power density of 0.92 W cm-2 in H2–O2 PEMFC, which is comparable to state-of-the-art Fe–N–C catalyst. This strategy is helpful to synthesize highly active M-N-C ORR catalysts with improved mass transfer and electric conductivity. [Display omitted] •Porous carbon supporting to prevent the aggregation of ZIF8 particles.•A high-performance ZIF-based Co–N–C catalyst is fabricated.•A remarkable peak power density of 0.92 W cm-2 in H2–O2 PEMFC.